Konflik Antara Hukum Adat dan Hukum Nasional: Kasus Kawin Tangkap di Sumba - Djaga Mesa, Grendhard; Putra Frans, Mardian (UNES Law Review, 2024)
This study aims to investigate the conflict between customary and national laws in Sumba Barat Daya, particularly concerning the controversial practice of "kawin tangkap" (forced marriage). The primary objective is to analyze the impact and dynamics of this legal conflict, focusing on human rights violations, especially those affecting women, and to explore solutions to alleviate tensions between customary and national laws. The research methodology employs a qualitative approach, gathering data from various reliable online news sources, conducting interviews, and analyzing public opinions. Thematic data analysis is utilized to identify different perspectives, arguments, and policy implications. Thus, this research integrates legal, human rights, and policy perspectives on the legal conflict in Sumba Barat Daya, providing relevant policy recommendations to address the issues at hand.